Hangman blind [large type] - Clark, Cassandra (Clark, Cassandra. Abbess of Meaux mysteries., 2009)
In November 1382, the month of the dead, Abbess Hildegard rides out for York from the Abbey of Meaux. This is no ordinary journey--it is a time of rival popes, a boy king, and a shaky peace in the savage aftermath of Wat Tyler's murder--and Hildegard has embarked on a perilous mission to try to secure the future of her priory.